Peningkatan Literasi Digital Anak Melalui Penyuluhan Dunia Digital yang Aman dan Bijak di RT.002 RW.009, Kelurahan Kwitang - Ade Suryadi; Ricki Sastra; Suharyanto Suharyanto; Siti Khotimatul Wildah; Siti Laila Wahyuni; Khaila Anjani; Siti Nurjanah; Muhamad Iqbal Irsyad (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
This community service program aims to improve children's digital literacy in RT.002 RW.009, Kwitang Subdistrict through structured educational outreach. The method applied is a participatory action research approach, involving pre- and post-test assessments using a digital literacy questionnaire. The results showed a significant increase in the average literacy score from 55.3 (pre-test) to 82.6 (post-test), confirming the effectiveness of the intervention. Key improvements were observed in awareness of online safety, understanding of hoaxes, and ethical social media use. This initiative contributes to informed and secure digital behavior in urban communities.